Detection of olive oil mill waste (OOMW) disposal areas using high resolution GeoEye's OrbView-3 and Google Earth images - Agapiou, Athos; Papadopoulos, Nikos G.; Sarris, Apostolos (My University, 2016)
© 2016 A. Agapiou et al. The olive oil industry is considered to be as one of the driving sectors of the agricultural economy of the Mediterranean basin. The extraction of olive oil generates huge quantities of wastes that may have a great impact on land and water environments due to high concentrations in phenolic compounds that could cause ophytotoxicity. This paper aims to examine the potential use of freely distributed satellite images for the detection of olive oil mil waste (OOMW) areas in the island of Crete through the use of two cases studies. In the first case study an archive GeoEye OrbView-3 image was used to detect OOMW areas using the Spectral Angle Mapper detection algorithm and other geometric and topographic parameters. In the second case study, Google Earth images were examined through different classification algorithms at different scales. The overall results demonstrate that remote sensing techniques can be used as an alternative to field observations so as to detect and monitor OOMW areas Furthermore, freely distributed RGB images from digital globes (such as Google Earth) can be sufficiently and effectively used for this purpose.
Keywords: Classification; Disposal areas; GeoEye OrbView-3; Google Earth; Olive mill waste water